Pengaruh Pemberian Air Kelapa terhadap Perkembangan Embrio pada Dendrobium anosmum Lindl - Astriani Dewi, Ni Putu Yuni (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
The aim of the research is to find out effect of addition of coconut water in the media to the number of last stage D. anosmum Lindl embryo. Research was conducted at the Plant Structure and Development of Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences University of Udayana and UPT. Balai Benih Induk Tanaman Pangan dan Hortikultura Provinsi Bali from February 2015 to July 2015. Three type of media were employed, i.e. PDA, Organic, MS. Three different concentration of coconut was added to media, i.e. 0 ml/L 50 ml/L, 100 ml/L. Results showed that addition of 100 ml / L coconut water in MS showed that media is capable to increase the formation of final stages embryos (> 32 cells).